Brest Catechism (1553). The Confesional and Cultural Background of the First Publication of the Printing House in Brest - Chemperek, Dariusz (Knygotyra, 2023)
The aim of the article is to answer the question about the sources of inventio of the so-called Katechizm brzeski [Brest Catechism] showing the confessional and cultural basis of this print published in Brest-Litovsk in the first year of this publishing house’s operation. Printed in 1553, and created by an unknown writer, Katechizm brzeski is a product of various confessional tendencies and aspirations – religious, cultural and political – of the Lithuanian political class in the second half of the 16th century. The conclusions of the article are as following: 1. Katechizm brzeski was published in the second half of 1553. 2. This theologically eclectic catechism is an attempt to find iunctim between Martin Luther’s and John Calvin’s influences. The Lutheran influences prevail. 3. Katechizm brzeski’s author used not only the catechism of Jan Seklucjan (1544), but also two works by Urban Rhegius (catechism from 1543, Medicina animae in the Polish translation, 1551) and Catechismus minor (1527–1528) by Johannes Brenz. 4. The compiler was well versed in the Osiandrian controversy taking place in the 1550s in the nearby Ducal Prussia. As a supporter of Andreas Osiander, the compiler applied to the Katechizm brzeski his optimistic anthropology to the newest – formally Calvinist – catechism.
Keywords: Katechizm brzeski; Brest printing house; Mikołaj Radziwiłł the Black; Bernard Wojewódka